PREVENTION AND TREATMENT OF LOW BACK PAIN: EVIDENCE, CHALLENGES, AND PROMISING DIRECTIONS - ⁠ Waad Majed Almutairi; Ibrahim mohammed alyami; Yazeed Abdulrhman Alghamdi; Saadyh Farhan Alshammri; Daliya Mohammed alabbasi; Atheer Hussain Aljarullah; Saad Mohammed Saad Alzuair; Muteb Mohammed Nasser Alharbi; Samar Khalid Arif Salamah (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Introduction: Back pain represents a significant occupational hazard for dental professionals, affecting their health, productivity, and quality of life. Given the high prevalence of musculoskeletal disorders in this group, there is a critical need for effective prevention strategies. This systematic review aimed to evaluate the effectiveness of interventions designed to prevent back pain among dental professionals, focusing on ergonomic adjustments, physical exercise programs, and mindfulness interventions. Methods: A comprehensive literature search was conducted across multiple databases, including PubMed, Cochrane Library, Scopus, Web of Science, and CINAHL, to identify interventional studies and clinical trials published in the last 20 years (2002 to 2022). The search strategy utilized keywords related to back pain prevention, dental professionals, and various intervention types. Studies were included if they were interventional research focusing on back pain prevention among dental professionals. The selection process involved rigorous screening, data extraction, and synthesis, adhering to predefined inclusion and exclusion criteria. Results: Ten studies met the inclusion criteria, demonstrating a diverse range of interventions. Ergonomic interventions, such as the use of adjustable chairs and magnification loupes, showed a 35% reduction in back pain incidence (RR 0.65). Physical exercise programs tailored to dental professionals reported a 40% reduction in back pain episodes (RR 0.60). The evidence on mindfulness interventions was promising but preliminary, indicating potential benefits for stress reduction and pain management. The review highlighted the synergistic effect of combining multiple interventions, suggesting a multifaceted approach could offer the most significant benefits. Conclusions: The systematic review provides compelling evidence that targeted ergonomic and physical exercise interventions are effective in significantly reducing the risk of back pain among dental professionals. These interventions should be considered essential components of occupational health programs in dental settings. Future research should explore the integration of multiple preventative strategies and further investigate the role of mindfulness and stress management interventions.